Reorganizing the Local Boy Scouts Associations in the Northern Province of the Gold Coast Colony - Essah, Doris Susannah (Cultural and religious studies, 2018)
Imperialist Robert Baden-Powell’s Boy Scouts Association started in the Gold Coast Colony during the First World War and schooled boys for nationality during the 1920s. This paper uses archival documents to discuss how Chief Scout Governor Gordon Guggisberg, who was brigadier general during the First World War, reorganized the Boy Scouts Association in the Northern Province of the Northern Territories Protectorate. The scout officers at the Local Boy Scouts Associations had the power to fashion desire but were not supposed to have consequences on political power. As government officers and scout officers they had warrants to work at the government schools at Gambaga, Wa, and Lawra to attain money locally for kits to instruct and invent the identity, customs and nationalist categories of schoolboys performing the British Empire.